Епокси-дерев'яні вироби як елемент свідомого споживання - Гадаєва, Ю. С.; Тихомирова, Тетяна Сергіївна; Лебедєв, Володимир Володимирович (Західно-Український Консалтинг Центр, ТзОВ, 2021)
Wooden furniture and other interior elements are in demand in the market regardless of the country and general fashion trends. This is due to the environmental friendliness of wooden products, the use of renewable resources for their production, long-term operation and the possibility of repair. Still, modern fashion trends have an impact on the range of wooden products and their . For the last 5 years, designers have paid special attention to the combination of different materials in one product. Among such materials, the most common are wooden products in combination with epoxy resins. Environmental impact of epoxy - wood production is shown in this work.
Keywords: вторинне використання; відновлювальний ресурс; тверді відходи; епоксидні смоли